1996
DOI: 10.3354/ame010115
|View full text |Cite
|
Sign up to set email alerts
|

Ratios of carbon, nitrogen and phosphorus in Pseudomonas fluorescens as a model for bacterial element ratios and nutrient regeneration

Abstract: Bactena play a sign~ficant role in the nutnent dynamics of plankton~c systems, yet the11 nutrient demands are poorly known Heie, we charactenze the element latios of a common freshwater bactenum relative to growth rate and nutrient availability P s e~~d o m o n a s fluorescens was grown in chemostats at dilution rates of 0 03 0 06, and 0 09 h ' Phosphorus (P) was supplied at approximately 5 ~.IM and nitrogen (N) was supphed at varylng concentlatlons to establish resource molar-N P ratios (SNP) ranglng between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 21 publications
6
67
0
1
Order By: Relevance
“…PNP produced from paraoxon represses cell growth. It has been reported that PNP is cytotoxic and represses growth (4,19). When PNP accumulated in the medium to a high concentration, cell growth, and hence paraoxon degradation, ceased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PNP produced from paraoxon represses cell growth. It has been reported that PNP is cytotoxic and represses growth (4,19). When PNP accumulated in the medium to a high concentration, cell growth, and hence paraoxon degradation, ceased.…”
Section: Resultsmentioning
confidence: 99%
“…The strains and plasmids used are listed in Table 1 4 , with C and P sources added separately (24)] was used for in vivo assays of paraoxon degradation. This medium allows fine manipulation of phosphate and carbon sources.…”
Section: Methodsmentioning
confidence: 99%
“…L239 was stratified during the period of sampling, and its seston C:P and C:N ratios (Table 1) suggested severe nitrogen and phosphorus deficiency of phytoplankton throughout the growing season (Healey & Hendzel 1980). If stoichiometric ratios in the seston also characterize bacterioplankton, then phosphorus limitation is likely (Vadstein & Olsen 1989, Chrzanowski & Kyle 1996.…”
Section: Methodsmentioning
confidence: 99%
“…However, a few studies have observed limited elemental plasticity of aquatic bacteria (e.g., TEZUKA, 1990;CHRZANOWSKI and KYLE, 1996), and there is some evidence that fungi respond to low phosphorus by storing phosphorus in polyphosphate granules, reducing the phosphorus content of cell walls, and partially replacing phospholipid with phosphorus-free lipid (BEEVER and BURNS, 1980;JENNINGS, 1995).…”
mentioning
confidence: 99%